STEM-PBL Based Learning: Digital Student Worksheet Simulation aided by PhET to Improve Students' Critical Thinking Skills in Science Learning - Muhammad Ikhsan; Rusdiman Buhera; Patar Ariyanto S.; Luqmanul Hakim Abiabdillah; Sabar Nurohman; Ismail Fikri Natadiwijaya (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2025)
This study aims to develop and evaluate the validity, practicality, and effectiveness of STEM-PBL digital worksheets assisted by PhET simulation to improve critical thinking skills of junior high school students. The research design used the 4D model combined with Research and Development (R&D). The limited field test involved 10 junior high school students, while validation was conducted by 4 experts. The extensive field test with pretest-posttest design involved 94 seventh grade students from three classes. Data were collected through tests, questionnaires, and observations. Quantitative data analysis used statistical tests, while qualitative data were analyzed descriptively with percentages. The results showed that the PhET simulation-assisted STEM-PBL digital worksheet had high content and construct validity (average 0.91 and 0.97). The practicality of the worksheet was also very high (92.8%). The effectiveness is evidenced by the significant difference in N-gain (sig 0.002 <0.05) which shows a significant difference in critical thinking skills between the experimental and control classes. In conclusion, the PhET simulation-assisted STEM-PBL digital worksheet is valid, practical, and effective for density topics in science learning.